1999
DOI: 10.1002/chin.199947033
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Sn3N4, a Tin(IV) Nitride — Syntheses and the First Crystal Structure Determination of a Binary Tin—Nitrogen Compound.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…Spinel-type silicon nitride γ-Si 3 N 4 is a high-pressure phase of silicon nitride and has been discovered in 1999 1 . In the same year, from the group 14 element, spinel type Ge 3 N 4 2 and Sn 3 N 4 3 have been found afterwards. Based on these experimental findings, Ching et al predicted a variety of binary and ternary nitrides including nitrides of transition metal elements 4 .…”
mentioning
confidence: 89%
“…Spinel-type silicon nitride γ-Si 3 N 4 is a high-pressure phase of silicon nitride and has been discovered in 1999 1 . In the same year, from the group 14 element, spinel type Ge 3 N 4 2 and Sn 3 N 4 3 have been found afterwards. Based on these experimental findings, Ching et al predicted a variety of binary and ternary nitrides including nitrides of transition metal elements 4 .…”
mentioning
confidence: 89%
“…0.02% Cr) [182], GaN:Zn and GaN:Mg [211]. Cubic tin nitride Sn 3 N 4 has been reported to form from SnI 4 or SnBr 4 with KNH 2 in liquid (but not supercritical) ammonia at 243 K followed by annealing in vacuo at 573 K [212].…”
Section: Group III and Iv Nitridesmentioning
confidence: 99%
“…In 1999, independent studies using synchrotron X-ray diffraction and Raman spectroscopy first revealed the cubic spinel-structured (γ−) polymorphs of the ceramic phases Si 3 N 4 and Ge 3 N 4 [39,40]. These constituted the first examples of the new class of nitride spinels, that were soon joined by the remaining group 14 member Sn 3 N 4 , initially prepared by chemical reaction techniques at near-ambient conditions [41] and later by HPHT synthesis [42]. The new nitride spinels have potentially useful optoelectronic properties including wide, direct bandgaps in the blue-UV range, comparable with (Ga,In,Al)N solid solutions [43][44][45] volume press syntheses that allowed structure determination by Rietveld refinement of powder X-ray diffraction data [39,40], and later led to preparation of γ-(Si,Ge) 3 N 4 solid solutions and intermediate compounds [46].…”
Section: Transition Metal Nitridesmentioning
confidence: 99%